Embodied Agency and Divine Healing: A Historical Theological Analysis of Women in Pentecostal Tradition - Ginting, Aldrik Christian Prayfanca; Debora, Rogate; Momongan, Yefta (STT Iman Jakarta, 2025)
The question of women’s participation in divine healing remains significant within Pentecostal theology, which affirms the universality of the Spirit’s gifts yet often limits women’s embodied agency in practice. This study addresses the gap between theological potential and ecclesial reality by examining how women’s bodies function as instruments of divine healing rather than passive vessels. Using a qualitative historical-theological literature review supported by narrative analysis, the research interprets biblical, patristic, medieval, and Pentecostal texts that portray women as active participants in healing events, with attention to gestures, presence, and embodied acts that reveal cooperation between the embodied helper and the Divine Helper. The findings show that women across different periods exercised agency through physical action, symbolic gestures, ascetic practices, and relational presence, each serving as a locus where divine power becomes visible. These patterns demonstrate that healing arises through a synergistic partnership between human embodiment and the work of the Holy Spirit. The study concludes that recognizing women’s embodied agency is essential for a coherent Pentecostal theology of healing while calling churches to affirm and cultivate women as legitimate agents of divine healing.